Epstein–Barr Virus: Diseases Linked to Infection and Transformation - Jha, Hem C.; Pei, Yonggang; Robertson, Erle S. (Frontiers in Microbiology, 2016)
Epstein-Barr virus (EBV) was first discovered in 1964, and was the first known human tumor virus now shown to be associated with a vast number of human diseases. Numerous studies have been conducted to understand infection, propagation and transformation in various cell types linked to human diseases. However, a comprehensive lens through which virus infection, reactivation and transformation of infected host cells can be visualized is yet to be formally established and will need much further investigation. Several human cell types infected by EBV have been linked to associated diseases. However, whether these are a direct result of EBV infection or indirectly due to contributions by additional infectious agents will need to be fully investigated. Therefore, a thorough examination of infection, reactivation and cell transformation induced by EBV will provide a more detailed view of its contributions that drive pathogenesis. This undoubtedly expand our knowledge of the biology of EBV infection and the signaling activities of targeted cellular factors dysregulated on infection. Furthermore, these insights may lead to identification of therapeutic targets and agents for clinical interventions. Here we review the spectrum of EBV-associated diseases, the role of the encoded latent antigens, and the switch to latency or lytic replication which occurs in EBV infected cells. Furthermore, we describe the cellular processes and critical factors which contribute to cell transformation. We also describe the fate of B-cells and epithelial cells after EBV infection and the expected consequences which contribute to establishment of viral-associated pathologies.